Breast Cancer Illness and Spiritual Healing - Sulaiman, Szariannie; Mohd Noor, Noor Azlan (Global Journals™, 2021)
Spirituality, religion and family play pivotal roles in addressing issues related to one’s illness experiences. The illness experiences were perceived as a moral-religious experience rather than a mere suffering due to bodily dysfunctions. Thus, this qualitative study aimed at exploring the concept of spirituality in the lives of young Malay breast cancer patients. An ethnographic fieldwork was carried out among 13 young Malay breast cancer patients in Klang Valley and several selected areas of Selangor, Malaysia. A purposive snowballing technique was employed to select the informants for the study. A series of in-depth interviews, phone and online interviews guided by semi-structured interview schedule and participant observation were carried out among the informants. It is evident from the study that the manifestation of spiritual experiences in relation to their breast cancer is attributed to the spiritual meaning of breast cancer illness, roles of family in providing spiritual support and medical pluralisation. The informants attributed their breast cancer illness as qada’ and qadar of Allah. They accented it as ujian (test) or balasan (divine punishment) for a good cause from Allah S.W.T. On this account, spiritual healing was sought as complementary to hospital treatment in searching a cure for breast cancer.